Prinsip As-Sulhu Dalam Penyelesaian Sengketa dalam Islam - Nurudin, Irfan (LIPI, 2016)
The tradition of resolving disputes or conflicts through peace efforts already developed Islam a long time ago, even before Muhammad task as the Apostles. The Islamic period in the companions also reflects the existence of a spirit to avoid and resolve conflict in a way best to put forward the principles of peace. This is not only applied to the problems related to family law and commerce, but also already penetrated in the field of social and political disputes. In Indonesia in various products positive law and the customary law applicable to always uphold the principles of peace, consensus discussion to resolve the dispute or conflict..